2020
DOI: 10.3390/ijms21082893
|View full text |Cite
|
Sign up to set email alerts
|

MAP Kinases Pathways in Gastric Cancer

Abstract: Gastric cancer (GC) is turning out today to be one of the most important welfare issues for both Asian and European countries. Indeed, while the vast majority of the disease burden is located in China and in Pacific and East Asia, GC in European countries still account for about 100,000 deaths per year. With this review article, we aim to focus the attention on one of the most complex cellular pathways involved in GC proliferation, invasion, migration, and metastasis: the MAP kinases. Such large kinases family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 108 publications
0
26
0
Order By: Relevance
“…Mitogen-activated protein kinase (MAPK), mainly consisting of three distinctive cascades, the JNK, p38 and ERK pathways, is a well-known and crucial signaling pathway in multiple diseases (58)(59)(60)(61). In the past decades, the role of MAPK cascade in the TGF-β1-relevant IPF has been gradually elucidated.…”
Section: Mapk-relevant Signaling Pathwaymentioning
confidence: 99%
“…Mitogen-activated protein kinase (MAPK), mainly consisting of three distinctive cascades, the JNK, p38 and ERK pathways, is a well-known and crucial signaling pathway in multiple diseases (58)(59)(60)(61). In the past decades, the role of MAPK cascade in the TGF-β1-relevant IPF has been gradually elucidated.…”
Section: Mapk-relevant Signaling Pathwaymentioning
confidence: 99%
“…To study the function of the ceRNA network, we performed KEGG and GO enrichment analysis on DEmRNAs in ceRNA, which are mainly enriched in the MAPK signaling pathway. In cancer, the constitutively active MAPK signaling pathway often leads to promotion of abnormal cell growth and tumorigenesis [ 17 ] such as liver cancer [ 18 ] and gastric cancer [ 19 ]. In colon cancer, HNF1A-AS1 upregulates OTX1 to activate the ERK/MAPK pathway [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The result of this process is the formation of the second messengers inositol triphosphate (IP3) and diacylglycerol (DAG), leading to the activation of multiple downstream signaling cascades and cytoplasmic calcium mobilization, including phosphatidylinositol 3-kinase (PI3K)/Akt, Ras/mitogen-activated protein kinase (MAPK), and Janus kinase/signal transducer and activator of transcription (JAK/STAT) pathways [ 11 , 51 , 52 ]. Abnormal activation of PI3K/Akt and Wnt/β-catenin pathways has been found to promote GC progression and poor prognosis of cancer patients, suggesting their potential therapeutic target for GC patients [ 11 , 53 , 54 , 55 ]. It has been shown that MAPK pathways alterations may lead to GC, including H. pylori MAPK-triggering to transform from gastric normal epithelium to GC development.…”
Section: Chemokines In Gastric Cancermentioning
confidence: 99%
“…It has been shown that MAPK pathways alterations may lead to GC, including H. pylori MAPK-triggering to transform from gastric normal epithelium to GC development. Moreover, the impact of the MAPKs in GC progression and metastasogenesis and the involvement of the dysregulated kinase pathways in GC encourage new studies on therapeutic drugs which might improve the survival of GC patients [ 55 ]. The study of Ji et al [ 56 ] demonstrated an immunoregulatory role of β-catenin signaling in GC and suggested the therapeutic potential of CCL28 blockade for the treatment of GC, because this chemokine was proved to be as a key linker between the oncogenic β-catenin signaling and the GC microenvironment.…”
Section: Chemokines In Gastric Cancermentioning
confidence: 99%